2022
DOI: 10.1038/s41467-022-29235-2
|View full text |Cite
|
Sign up to set email alerts
|

Serum proteomics links suppression of tumor immunity to ancestry and lethal prostate cancer

Abstract: There is evidence that tumor immunobiology and immunotherapy response may differ between African American and European American prostate cancer patients. Here, we determine if men of African descent harbor a unique systemic immune-oncological signature and measure 82 circulating proteins in almost 3000 Ghanaian, African American, and European American men. Protein signatures for suppression of tumor immunity and chemotaxis are elevated in men of West African ancestry. Importantly, the suppression of tumor immu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 75 publications
(80 reference statements)
1
20
0
Order By: Relevance
“…Men of African ancestry, including African American (AA) and Ghanaian men, have a disproportionately higher burden of lethal prostate cancer when compared to European American (EA) men 1,3 . This increased mortality burden could be partially attributed to unique risk factor pro les by population group, as well as distinct in ammatory and immune responses that drive cancer aggressiveness and impact survival, as we have shown 4 .…”
Section: Introductionmentioning
confidence: 68%
See 3 more Smart Citations
“…Men of African ancestry, including African American (AA) and Ghanaian men, have a disproportionately higher burden of lethal prostate cancer when compared to European American (EA) men 1,3 . This increased mortality burden could be partially attributed to unique risk factor pro les by population group, as well as distinct in ammatory and immune responses that drive cancer aggressiveness and impact survival, as we have shown 4 .…”
Section: Introductionmentioning
confidence: 68%
“…Association of clinical/socio-demographic characteristics with circulating fatty acids. In similar fashion to our previous proteomic study on these cohorts 4 , we assessed the associations of age, BMI, education, smoking, diabetes, and aspirin use with the abundance of individual circulating fatty acids (as continuous values) by means of multivariable linear regression models implemented by the function lm in the base R package stats (version 3.6.1). For each fatty acid, we tted the formula "fatty acid ~ age + bmi + education + smoking + diabetes + aspirin", which yielded the model's F-statistic and associated Fstatistic p value, as well as the intercept and regression coe cients with their associated standard errors (SE) and P values.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study by several authors of the present study reported that immune-oncology marker profiles differ between men of African and European descent, which was partly explained by ancestry. 24 To evaluate whether marker profiles influenced by the neighborhood environment, we examined potential associations with 6 serum proteomics-defined biological pathways based on measurement of these 82 immune-oncology markers. We restricted this examination to the control population to exclude a confounding effect of prostate cancer.…”
Section: Association Between Neighborhood Deprivation and Serum Prote...mentioning
confidence: 99%